Adeline Gavin: capstone - Gavin, Adeline, artist (Colorado State University. Libraries, 2015)
The artist's statement: Life without emotion does not exist. Love without passion is not love. For me, art has become a deep and constant affair with materials and meanings. Sometimes I create with a clear purpose and I make exactly what I desire to create. Other times, I create for the pure joy of exploring materials. I enjoy constructing pieces that have meaning and substance but also beauty and elegance. The process of exploration, growth and struggle all play into my constant desire for this process in my daily life. Recently, I have been focusing on embracing personal independence and strength. I believe that finding acceptance and peace in solitude is important as an artist and an individual. Growth has always been an overarching theme that I have been drawn to. The idea of cherishing every stage of growth and existence is not always easy. However, I believe we should embrace each unique moment. Passion has led me as an artist to see the unique beauty within every stage of life, even failure and loss. Growing from such situations is where true beauty and strength lies.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing and jewelry